Flow and Fracture of Metals and Alloys in Nuclear Environments 1965
DOI: 10.1520/stp43532s
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Temperature and Irradiation on the Mechanical Properties of Austenitic Stainless Steels

Abstract: Work performed under Contract No. AT(45-1)-1830 between the Atomic Energy Commission and Battelle Memorial Institute

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Figure 64 illustrates the effect of irradiation on the roomtemperature yield strength and ductility. (134) xhe results indicate that a saturation in irradiation effects is reached after a fast fluence of about 2 x 10^0 n/cm^ if the irradiation is performed at 50 C. However, no saturation in irradiation effects is reached after a fast fluence of 1. 5 x 10^1 n/cm^ if the irradiation temperature is 290 C. The same trends, as far as saturation of irradiated effects, appear to take place for both the annealed and cold-worked (25 percent) material.…”
Section: Austenitic Stainless Steelsmentioning
confidence: 82%
See 3 more Smart Citations
“…Figure 64 illustrates the effect of irradiation on the roomtemperature yield strength and ductility. (134) xhe results indicate that a saturation in irradiation effects is reached after a fast fluence of about 2 x 10^0 n/cm^ if the irradiation is performed at 50 C. However, no saturation in irradiation effects is reached after a fast fluence of 1. 5 x 10^1 n/cm^ if the irradiation temperature is 290 C. The same trends, as far as saturation of irradiated effects, appear to take place for both the annealed and cold-worked (25 percent) material.…”
Section: Austenitic Stainless Steelsmentioning
confidence: 82%
“…It was found that irradiation did not cause any detectable increase in ferrite content, as measured by magnetic susceptibility. (134) Predominantly Fast Fluence Tensile Properties. The effect of irradiation in a predominantly fast fluence on the tensile properties of Type 304 stainless steel is illustrated in Figure 72.…”
Section: Austenitic Stainless Steelsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,3 There are, however, somewhat more published data on AISI 347, reaching both lower and higher exposures. 5,6,7 The perceived primary advantage of AISI 348 stainless steel in the nuclear community has been its lower activation due to lower levels of easily activated, long-lived impurities, especially Co.…”
Section: Comparison Of Aisi 347/348 With Other 300 Series Stainless Smentioning
confidence: 99%